Effective Advertising : Understanding When, How, and Why Advertising Works. - Tellis, Dr. Gerard J. J. (Marketing for a new century., 2003)
Understanding Effective Advertising: How, When, and Why Advertising Works reviews and summarizes an extensive body of research on advertising effectiveness. In particular, it summarizes what we know today on when, how, and why advertising works. The primary focus of the book is on the instantaneous and carryover effects of advertising on consumer choice, sales, and market share. In addition, the book reviews research on the rich variety of ad appeals, and suggests which appeals work, and when, how, and why they work. The first comprehensive book on advertising effectiveness, Underst.